Em nome da pátria : as manifestações contra o eixo em Santa Maria, 18 de agosto de 1942 - Dalmolin, Cátia Regina Calegari (2006)
August of 1942 mercant ships were plummeted in Brazilian seacoast by the axis (Germany, Italy and Japan) by provoking about 600 deaths. Feelings of revolt and indignation were widened in the country. In Santa Maria city, Ateneu Graça Aranha, The Democratic Youth Space, the politicians and the railway class promoted a monster-meeting of brasility in the shore of railway, which were widened along with the main streets of the city. On August 18th, 1942 A Razão Newspaper reported that the population from Santa Maria had lived patriotic exaltation moments by showing off and protesting openly aversion against the aggression from the Axis countries. These strong manifestations ended up with sacks and confusion to German-Brazilian and Italian-Brazilian places. Afterwards the foreigners were obligated to publish a local newspaper; the orders to people from Santa Maria in which they used a patriotic rethoric to explain that they were brazilian and with that to try avoiding new conflicts